(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article provides a detailed description of research conducted on the prevalence of dominant ectoparasites found in poultry farms and households in the Nukus city area of the Karakalpakstan Republic during the hot season of the year, as well as measures to prevent their spread.